Quality Assurance in Spices and Spice Products - Modern Methods of Analysis - Zachariah, K V Peter, T John (Journal of Spices and Aromatic Crops, 2000)
Spices spice the food of humans and play an important role in making our food palatable. Many spices are important in flavouring and seasoning of foods and form major ingredients in beverages and pharmaceuticals.